Communicating About COVID-19 in Four European Countries: Similarities and Differences in National Discourses in Germany, Italy, Spain, and Sweden - Sjölander-Lindqvist, Annelie; Larsson, Simon; Fava, Nadia; Gillberg, Nanna; Marcianò, Claudio; Cinque, Serena (Frontiers in Communication, 2020)
The pandemic spread of COVID-19 grew inexorably to be the main topic of global news after it was first identified in 2019 in China. This article analyzes how heads of state and heads of government in Germany, Italy, Spain, and Sweden framed the problems and solutions to the spread of the virus during the pandemic’s initial phase. A Foucauldian-inspired method of problematization guides the narrative analysis, complemented by governmentality, risk communication, and taskscape theories. The results of the analysis show how the individual is conceptualized as a central actor and whose practices are framed as crucial to overcoming the crisis. Through invoking a sense of responsibility, sacrifice, and current life during the pandemic as a difficult time, the speeches allude to how people through changed behavior can/sould, contribute to the greater good. The individual is positioned as a key cause of, and solution to the problem; however, construing the individual as an indispensable actor to overcoming the crisis also means that the individual is laid open for reprehension. To facilitate the spread of the containment message and to support individual understanding of overt risk, the four countries’ leadership also augment their conceptualization of the crisis with ideas of national identity to inspire the individual to contribute to the “battle” and “defeat” of the virus. The leadership does also embrace the important role of the national government in controlling the outbreak and the role of science, and trust in science, are also emphasized. The speeches analyzed in this paper can be understood as governance technologies; the spatial disciplining and self-governance demanded by the regimes create subject positions for individuals or groups. A debate on the rights and responsibilities of the citizen is another aspect that comes to the fore, considering how the containment strategies in all four countries proclaim the individual as a core agent in circumscribing the virus, and hence the individual’s activities as potentially damaging to the fight against the pandemic. This throws into question the connection between individual autonomy as a democratic right and disciplinary mechanisms, sometimes phrased encouragingly and at other times in an enforcing way.